Disseminated talaromycosis: an AIDS defining fungal infection - Devi, Bijayanti; S., Sana; Meka, Bharath; Raj, Bhuvanesh (International Journal of Research in Dermatology, 2020)
Talaromycosis is a systemic mycosis caused by Talaromyces marneffei. It mostly occurs as an opportunistic infection in patients with human immunodeficiency virus (HIV). In India, its endemic in Manipur. We report 3 cases of disseminated talaromycosis with skin eruptions in HIV sero-positive patients from Manipur.